Development of electrochemical oxidase biosensors based on carbon nanotube-modified carbon film electrodes for glucose and ethanol - Gouveia-Caridade, Carla (2008)
Functionalised multi-walled carbon nanotubes (MWCNTs) were cast on glassy carbon (GC) and carbon film electrodes (CFE), and were characterised electrochemically and applied in a glucose-oxidase-based biosensor. MWCNT-modified carbon film electrodes were then used to develop an alcohol oxidase (AlcOx) biosensor, in which AlcOx-BSA was cross-linked with glutaraldehyde and attached by drop-coating. The experimental conditions, applied potential and pH, for ethanol monitoring were optimised, and ethanol was determined amperometrically at -0.3 V vs. SCE at pH 7.5. Electrocatalytic effects of MWCNT were observed with respect to unmodified carbon film electrodes. The sensitivity obtained was 20 times higher at carbon film/MWCNT-based biosensors than without MWCNT.